2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627518
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a synergistically controlled semiautomatic trepanation system for neurosurgery

Abstract: One of the most common procedures in neurosurgery is the trepanation of the skull. In this paper, a synergistically controlled handheld tool for trepanation is introduced. This instrument is envisioned to reduce problems of dural tears and wide cutting gaps by combining a soft tissue preserving saw with an automatic regulation of the cutting depth. Since usability and safety of the semi-automatic handheld device are of utmost importance, the complex interaction between the user and the system has been analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…As the minimal residual inaccuracies of CT image segmentation as well as registration and tracking are in the order of magnitude of 1–2 voxels, that is, 0.5–1 mm, 19 image-based robotic bone dissection has to preserve the final internal cortical layer adjacent to the dura and underlying soft tissue. 4,16 By contrast, Follmann et al 7 demonstrated that a dura mater displacement of up to 2 mm is possible without undesired soft tissue damage using the STS approach with a soft-tissue-preserving saw. However, preoperative CT data acquisition, intraoperative registration, and dynamic tracking are also required.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…As the minimal residual inaccuracies of CT image segmentation as well as registration and tracking are in the order of magnitude of 1–2 voxels, that is, 0.5–1 mm, 19 image-based robotic bone dissection has to preserve the final internal cortical layer adjacent to the dura and underlying soft tissue. 4,16 By contrast, Follmann et al 7 demonstrated that a dura mater displacement of up to 2 mm is possible without undesired soft tissue damage using the STS approach with a soft-tissue-preserving saw. However, preoperative CT data acquisition, intraoperative registration, and dynamic tracking are also required.…”
Section: State Of the Artmentioning
confidence: 99%
“…The STS device 7 has been adapted to our needs to realize a first prototype of a saw suitable for in-process bioimpedance measurement.…”
Section: Integration Into the Sts Sawmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are IGS systems which reduce the speed of the surgical instrument as soon as sensitive anatomical structures are approached too closely or disable it entirely (instrument disablement, ID-IGS) (Labadie and Fitzpatrick, 2011;Strauss et al, 2005;Strauss et al, 2007), or restrict the movement of the instrument attached to a robotic arm (movement restriction, MR-IGS) (Lim et al, 2016). Other systems automatically control the cutting depth based on navigation information while the surgeon freely moves the instrument on the skull surface (semiautomatic trepanation system, STS-IGS) (Follmann et al, 2010).…”
Section: Igs System Functionalitiesmentioning
confidence: 99%
“…Using preoperatively acquired data and position tracking, the skull thickness at each site can be determined automatically during the cutting process. 10 Therefore, a reliable algorithm and mechanism to perform real-time skull thickness determination and automatic depth control was developed. 6 The cutting accuracy of the STS was evaluated in another test series on two phantom skulls without any relevant overcutting/undercutting errors.…”
Section: Introductionmentioning
confidence: 99%